Structural decomposition-based energy consumption modeling of robot laser processing systems and energy-efficient analysis. (August 2022) - Zhou, Jin; Yi, Hao; Cao, Huajun; Jiang, Pei; Zhang, Chaoyong; Ge, Weiwei
Highlights: Generalized motion EC models of main functional units of the RLPS were established, while the computational complexity of EC was analysed. A structural decomposition and modeling method of EC was proposed for the IR, to achieve rapid EC calculation of IRs. The energy-saving planning problems were analyzed for a laser processing IR welding complex parts. Abstract: Energy efficiency has been one of the main issues in manufacturing. Rapid energy consumption (EC) calculation is the key to improving the efficiency of EC optimization. In this paper, rapid EC calculation of robot laser processing systems (RLPSs) is studied based on structural decomposition. Firstly, the generalized motion EC models of main functional units of RLPSs are established for manufacturing processes, while the power consumption characteristics and computational complexity of EC are analyzed. Then, a modeling method of EC is proposed for industrial robots (IRs), based on structural decomposition, considering the generating mechanisms and computational complexity of EC. The models of all EC components are established, which are all parameterized functions of time or key factors (joint angle paths of the robot and the average acceleration of the end-effector). Moreover, EC models of other functional units are also well established according to the corresponding EC characteristics. A KUKA robot case is described to verify the proposed method. The results show that the established EC model of the IR has reliable prediction accuracy within the feasible speed range, which can well reflect the characteristic relationships between EC and time. The proposed study solution is also suitable for EC modeling of other robot manufacturing systems. Furthermore, the energy-saving planning of processing complex parts are analyzed for a laser processing IR. The RLPS has considerable energy-saving potentials under situations concerned.